Counseling and Exercise for the Community of Kubu Gulai Bancah Village, Bukittinggi: Pendidikan Kesehatan dan Senam Jantung Sehat Bagi Masyarakat Kelurahan Kubu Gulai Bancah, Bukittinggi - Suwandi, Febrian R; Sari, Dian; Gusmiati, Rita; Nike Puspita Alwi; Muhammad Pauzi; Rahmi Kurnia Gustin; Tika Ramadanti; Vera Kurnia (Ruang Ide Publisher, 2023)
Cardiovascular disease is a non-communicable disease with an increasing incidence yearly. Cardiovascular disease if not prevented can cause various problems such as cerebrovascular disorders, kidney disease, and others. Therefore, Prima Nusantara University Bukittinggi through a team of lecturers from the Faculty of Nursing and Public Health is conducting community service to increase public knowledge and awareness in the Kubu Gulai Bancah Village, Bukittinggi City of the importance of having a Healthy Heart. Community service activities were carried out through several activities, namely health checks, exercises, and counseling which were attended by around 30 participants in the Kubu Gulai Bancah Village, Bukittinggi City. The results of community service increased participants' knowledge about cardiovascular diseases. This series of activities can be continued into routine activities every week and can be applied to different topics.